2021
DOI: 10.1136/tsaco-2021-000777
|View full text |Cite
|
Sign up to set email alerts
|

Damage control laparotomy in trauma: a pilot randomized controlled trial. The DCL trial

Abstract: BackgroundAlthough widely used in treating severe abdominal trauma, damage control laparotomy (DCL) has not been assessed in any randomized controlled trial. We conducted a pilot trial among patients for whom our surgeons had equipoise and hypothesized that definitive laparotomy (DEF) would reduce major abdominal complications (MAC) or death within 30 days compared with DCL.MethodsEligible patients undergoing emergency laparotomy were randomized during surgery to DCL or DEF from July 2016 to May 2019. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…111 A single-institution RCT trended toward improved outcome with damage-control laparotomy. 112 However, damage-control surgery has also been associated with significant rates of intra-abdominal infection, enterocutaneous fistula, and ventral hernia formation, including when compared with matched controls. 113 A 2016 report identified the following indications most highly associated with use of damage-control surgery: injury pattern identified during operation, inability to control hemorrhage, greater volume of resuscitation required, severity of physiologic insult, and need for staged abdominal or thoracic wall reconstruction.…”
Section: Abdominal Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…111 A single-institution RCT trended toward improved outcome with damage-control laparotomy. 112 However, damage-control surgery has also been associated with significant rates of intra-abdominal infection, enterocutaneous fistula, and ventral hernia formation, including when compared with matched controls. 113 A 2016 report identified the following indications most highly associated with use of damage-control surgery: injury pattern identified during operation, inability to control hemorrhage, greater volume of resuscitation required, severity of physiologic insult, and need for staged abdominal or thoracic wall reconstruction.…”
Section: Abdominal Injurymentioning
confidence: 99%
“…High-quality data regarding when to use damage-control rather than definitive surgery are lacking, and a 2021 systematic review confirmed inadequate evidence to draw conclusions regarding indication or effectiveness 111 . A single-institution RCT trended toward improved outcome with damage-control laparotomy 112 . However, damage-control surgery has also been associated with significant rates of intra-abdominal infection, enterocutaneous fistula, and ventral hernia formation, including when compared with matched controls 113 .…”
Section: Interventions/therapiesmentioning
confidence: 99%
“…Die Durchführenden stellten die Hypothese auf, dass durch eine definitive Versorgung die Rate an abdominellen Major-Komplikationen reduziert werden könne. Tatsächlich zeigte sich jedoch in der Studienpopulation ein tendenziell besseres Outcome der DCS-Gruppe bei geringerer 30-Tage-Morbidität und -Mortalität 14 .…”
Section: Therapieunclassified